Genome-Wide Differential Expression Profiling of Pulmonary circRNAs Associated With Immune Reaction to Pasteurella multocida in Goats - Chen, Qiaoling; Zhang, Zhenxing; Chen, Si; Chen, Jie; Cheng, Yiwen; Liu, Ang; Li, Bin; Chen, Zhen; Zheng, Yiying; Ga, Manchuriga; Du, Li; Wang, Fengyang (Frontiers in Veterinary Science, 2021)
Pasteurella multocida is a highly versatile pathogen that infects a wide range of animals, including goats, causing pneumonia and hemorrhagic septicemia. Circular RNA (circRNA) is a type of non-coding RNA that plays an important role in regulating cellular metabolism. However, whether and how circRNA is involved in regulating immune responses in the goat lung has not been reported. Thus, this study was designed to examine the function of circRNA in goats infected with Pasteurella multocida. Goats were assigned into one of two groups: an uninfected control group (CK) and an infected group challenged with P. multocida. Compared with the CK group, which remained healthy, the infected goats showed clinical signs of infection, including depression, cough, nasal discharge, and dyspnea, along with elevated body temperature and lesions in the lung. Whole-transcriptome sequencing and small RNA sequencing were then performed using lung samples from goats from each group. A total of 138 circRNA, 56 micro RNA (miRNA), and 2,673 messenger RNA (mRNA) molecules were significantly differentially expressed in the P. multocida-infected group compared with the CK group. Randomly-selected differentially-expressed circRNA, miRNA, and mRNA molecules (n = 5 per group) were then validated by quantitative reverse-transcriptase polymerase chain reaction analysis. Gene ontology (GO) analysis of the source genes indicated that six immune-related terms were enriched among the differentially-expressed cirRNA molecules, including inflammatory response, immune effector process, cell activation involved in immune response, cytokine-mediated signaling pathway, response to endogenous stimulus, and immune response. The corresponding circRNA molecules were then selected for construction of a competitive endogenous RNA network to identify networks that may be involved in the immune response to P. multocida infection. The results indicated that P. multocida HN01 may cause pneumonia and stimulate an immune response in goats via regulation of circRNA expression. This study presents the first comprehensive circRNA profile in response to P. multocida infection in goats, thus providing a basis for understanding the function of circRNA in the host immune response to P. multocida infection.